(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: This research investigates the impact of strategic tax planning, project tax planning, and operational tax planning on tax liability within Nepalese manufacturing companies. The primary objective is to assess the influence of tax planning practices on the tax liability among manufacturing companies in Nepal. Methods: Employing descriptive and causal research design, data were gathered through a structured questionnaire with responses measured on a Likert scale. The study engaged 387 respondents, providing a robust dataset to analyze tax planning practices in the Nepalese manufacturing company. Observing to a positivist philosophy and employing a deductive strategy, the research utilizes quantitative methods to rigorously test the formulated hypotheses. Results: Mean values of strategic tax planning, project tax planning, operational tax planning, management efficiency and tax liability have been found to be higher than 3.5. The findings also reveal that there is a significant relationship between strategic tax planning, project tax planning, operational tax planning and tax liability in Nepalese manufacturing companies. There is a mediating role of management efficiency on strategic tax planning, project tax planning, operational tax planning and tax liability. Conclusion: The results reveal a significant impact of tax planning on tax liability in Nepalese manufacturing companies. Management efficiency plays a mediating role in the relationship between tax planning and tax liability. The practical implications of this research extend to polcymakers, tax prodessionals, and corporate leaders. It also provides actionalble information for enhancing financial decision making with in the corporate sectors.